Tax Planning on Corporate Income Tax at PT Surya Cintapuri Pratama in 2023 - Susilawati Susilawati (Jurnal Ilmiah Multidisiplin, 2025)
This research is entitled "Tax Planning on Corporate Income Tax at PT Surya Cintapuri Pratama in 2023" which has not maximized Tax Planning. The aim is to describe how appropriate Tax Planning can minimize corporate income tax payments at PT Surya Cintapuri Pratama. This type of research uses primary data and quantitative research methods. The data used in this study is the annual financial report of PT Surya Cintapuri Pratama in 2023. In maximizing Tax Planning, the strategy that can be done is to make a nominative list related to entertainment costs, managing employee uniform expenses, managing employee medical expenses, managing policies on BPJS health and employment expenses, the use of methods gross-up in calculating employee salaries, management of health facilities, tax payments and reporting of tax due in accordance with applicable regulations and on time. The results showed that the tax planning resulted in tax savings of IDR 305.979.135. Tax Planning has a positive impact so that the cash flow available from tax savings can be maximized to support the company’s operational activities.